Ilmu pendidikan merupakan suatu Dasar Dasar History Sistem Pendidikan Nasional: Sistem Pendidikan Nasional - Bagus Setiawan , Artino Nanda; Maunah, Binti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
Abstract: National education is a method that stands on a foundation imbued with the philosophy of life of the nation which has the goal of serving the national aspirations and aspirations of a nation. Just like the education system during the Hindu-Buddhist era. The education system during the Hindu-Buddhist period was based on goals such as religion. While the education system during the Dutch East Indies era, the education system during the Dutch East Indies era was a form of hierarchy between the natives and the Dutch. The goals of the education system during the Dutch East Indies era were also different from the Hindu-Buddhist period. Education during the Dutch East Indies era put more emphasis on the mundane and the ability to be creative in order to obtain superior human resources keywords: national education system, history